The VCU Pressure Ulcer Summit: The Search for a Clearer Understanding and More Precise Clinical Definition of the Unavoidable Pressure Injury. Issue 5 (September 2016) - Alvarez, Oscar M.; Brindle, C. Tod; Langemo, Diane; Kennedy-Evans, Karen Lou; Krasner, Diane L.; Brennan, Mary R.; Levine, Jeffrey M.
Abstract : This article reports the findings of the Unavoidable Pressure Ulcer Committee (of the VCU Pressure Ulcer Summit) that was tasked with addressing key issues associated with pressure injuries that are unavoidable or unpreventable. Our goals were (1) to clarify nomenclature and descriptions surrounding "terminal ulceration, " (2) to describe the medical complications and comorbid conditions that can lead to skin failure and/or terminal ulceration, (3) to describe the variable possible causes of unavoidable pressure injuries, and (4) to present clinical cases to exemplify pressure injuries considered to be unavoidable.